Evaluation of new motorized articulating laparoscopic instruments by laparoscopic novices using a standardized laparoscopic skills curriculum - Uysal, Daniel; Gasch, Claudia; Behnisch, Rouven; Nickel, Felix; Müller, Beat P.; Hohenfellner, Markus; Teber, Dogu (Surgical endoscopy and other interventional techniques, 2021)
Motorized articulating laparoscopic instruments (ALI) offer more degrees of freedom than conventional laparoscopic instruments (CLI). However, a difficult learning curve and complex instrument handling are still a problem of ALI. We compared the performance of new prototypes of motorized ALI with CLI in a series of standardized laparoscopic tasks performed by laparoscopic novices. Further, usability of the new ALI was assessed.
Published online: 20 October 2020
Gesehen am 18.10.2021